Chitosan film of thiolated TPGS-modified Au-Ag nanoparticles for combating multidrug-resistant bacteria - Singh C.; Mehata A.K.; Viswanadh M.K.; Tiwari P.; Saini R.; Singh S.K.; Tilak R.; Tiwari K.N.; Muthu M.S. (My University, 2025)
The widely used vitamin-E based amphiphilic material, tocopheryl polyethylene glycol succinate (TPGS) was further improvised to redox-sensitive thiolated TPGS (TPGS-SH), which has been achieved by attaching 4-aminothiophenol. Further, TPGS and TPGS-SH-coated bimetallic gold-silver nanoparticles (TPGS-Au-Ag-NP and TPGS-SH-Au-Ag-NP) were formulated to explore their antibacterial and wound healing abilities. The prepared NP were monodisperse with a mean hydrodynamic diameter of 69.5±3.23 nm, 59.65±3.23 nm, PDI of 0.3±0.05, 0.2±0.03 and a zeta potential of +29.2±2.71 mV and +35.28±1.53 mV, respectively. The TPGS and TPGS-SH modified Au-Ag-NP were tested for their antibacterial efficacy against methicillin-resistant Staphylococcus aureus (MRSA) and E. coli; minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results showed that TPGS Au-Ag-NP, TPGS-SH-Au-Ag-NP displayed significantly stronger antibacterial activity than their coating material alone. The anti-efflux pump activity of the most potent antibacterial agent TPGS-SH-Au-Ag-NP was evaluated against MRSA. Toxicity assessment of TPGS-SH-Au-Ag-NP in human dermal fibroblasts showed 88% viability up to 125 µg/mL. The TPGS-SH-Au-Ag-NP, after incorporation in chitosan film (TPGS-SH-Au-Ag-NP-CS), exhibited sustained release and prolonged in vivo residence characteristics, which were evaluated by IVIS. Results also revealed that treatment with TPGS-SH-Au-Ag-NP showed a significant 87% wound healing rate after 12 days of application in the rat model. Hence, we concluded that TPGS-SH-Au-Ag-NP was safe and effective against test bacteria MRSA and capable of efficient wound healing when incorporated in chitosan film. © 2024 Elsevier B.V.